What kind of financing does agriculture need to create jobs and prevent climate change? - Balogun, Ayodeji; Hebebrand, Charlotte; Munene, Fred; Shetty, Shobha (World Bank, 2024)
It is expected that in 2050 there will be nearly 10 billion people in the world. As the population grows, we will need more farmers to produce more food. But the world’s food system is also a huge contributor of greenhouse gas emissions. This episode discusses how we can support small farmers and enterprises by providing the finance they need to produce food and supporting the jobs of the future, while reducing emissions.